KAJIAN YURIDIS UNDANG-UNDANG PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA DAN EFEKTIVITASNYA DI PENGADILAN AGAMA GARUT - Hopipah, Eva Nur; Mumtaz, Habib; Supriatna, Encup; Syarif, Nurrahman (Family Law Study Program, Faculty of Sharia and Law, UIN Sunan Gunung Djati Bandung, 2023)
Abstract Divorce cases continue to increase from time to time, whether divorce divorce or divorce lawsuit. And one of the causes that often occurs in this era is domestic violence. Juridically, especially in positive law, it has been regulated in the PKDRT Law (the Law on the Elimination of Domestic Violence), but in reality on the ground it is necessary to study its effectiveness because in reality cases of domestic violence continue to increase. This research is a case study at the Garut Religious Court. The number of divorce lawsuit decisions at the Garut Religious Court in January 2023 was 120, 104 were granted both present and without being attended in a verstek, occult and contra ditur. The implementation of the Court's decision is not all carried out effectively and as expected. So far, researchers have obtained data on approximately 20 cases for January. Its effectiveness is illustrated in three examples of the decisions of the Garut Religious Court with the alleged reason for the divorce being domestic violence. PA Garut's decision; number 138/Pdt.G/2023/PA.Grt, number 168/Pdt.G/2023/PA.Grt and number 199/Pdt.G/2023/PA.Grt. From the information on the decision, it can be said that the effectiveness of the PKDRT Law in the Garut Religious Court has not been effective for various reasons, one of the reasons is because divorce cases on the grounds of domestic violence in PA Garut have continued to increase despite the existence of the PKDRT Law.Â Keywords: PKDRT Law; Garut Religious Court; Domestic violenceÂ AbstrakKasus perceraian terus mengalami peningkatan dari waktu ke waktu, entah cerai talak ataupun cerai gugat. Dan salah satu penyebab yang sering kali terjadi di era ini adalah adanya KDRT. Secara yuridis, khususnya dalam hukum positif telah diatur dalam UU PKDRT (Undang-Undang Penghapusan Kekerasan dalam Rumah Tangga), namun dalam realita di lapangannya perlu dikaji efektivitasnya karena realitanya kasus KDRT terus mengalami peningkatan. Penelitian ini studi kasus di Pengadilan Agama Garut. Jumlah putusan gugatan perceraian di Pengadilan Agama Garut pada januari tahun 2023 sebanyak 120, 104 dikabulkan baik hadir maupun tanpa dihadiri secara verstek, ghoib dan kontra ditur. Implementasi dari putusan Pengadilan tidaklah semua terlaksana secara efektif dan sesuai harapan. Sejauh ini peneliti mendapatkan data kurang lebih 20 perkara untuk bulan januari. Efektivitasnya tergambar pada tiga contoh putusan Pengadilan Agama Garut dengan dugaan alasan perceraian adanya KDRT. Putusan PA Garut tersebut; nomor 138/Pdt.G/2023/PA.Grt, nomor 168/Pdt.G/2023/PA.Grt dan nomor 199/Pdt.G/2023/PA.Grt. Dari informasi putusan tersebut bisa di katakan bahwasannya efektivitas UU PKDRT di Pengadilan Agama Garut belum efektif dengan berbagai penyebab, salah satu sebabnya ialah karena kasus perceraian dengan alasan KDRT di PA Garut Â terus mengalami peningkatan meski sudah adanya UU PKDRT.Kata Kunci : UU PKDRT ; Pengadilan Agama Garut; Kekerasan dalam Rumah Tangga